Quantitative Evaluation of Joint Space Width in the Lateral Compartment after Medial Unicompartmental Knee Arthroplasty: Comparison of Three Radiographic Views - Yue, Ju'an; Guo, Wanshou; Wan, Fuyin; Wen, Pengfei; Liu, Zhaohui; Cheng, Liming; Zhang, Qidong; Chen, Yan (The Journal of Knee Surgery, 2018)
Lateral compartment cartilage deterioration is the most common complication affecting medial unicompartmental knee arthroplasty (UKA) survivorship. The purpose of this study was to determine the best method of judging the degeneration of cartilage in the lateral compartment after medial UKA through analysis of different radiographic views. Forty-two participants were divided into two groups. Patients in Group A were followed for at least 10 months after undergoing a medial UKA (mean: 17.67 ± 7.65 months, range: 10–24 months), whereas those in Group B were evaluated 3 days after surgery. Joint space width in the lateral compartment of all patients was evaluated using three types of knee radiographs: weight-bearing anterior posterior (AP), supine AP, and supine valgus stress. No difference in joint space width in the lateral compartment after medial UKA was found for the three kinds of radiographs in Group A (F = 0.97, p = 0.39) and Group B (F = 1.499, p = 0.233). After evaluating the patients 3 days after surgery or following them for approximately 18 months after medial UKA, we determined that weight-bearing AP, supine AP, and supine valgus stress knee radiographs were comparable when used to assess residual cartilage thickness of the lateral compartment.
Keywords: unicompartmental knee; radiograph; valgus; lateral compartment; cartilage